Parceria público-privada em presídios: (in)sustentabilidade da privatização e os novos desafios da gestão penitenciária na pós-modernidade - Santos, Daniel de Andrade (2017)
Brazil in recent decades has seen considerable increases in crime levels, especially in crime against property and drug trafficking. This condition reflects directly in the penitentiary system. Lacking and insufficient to supply current needs, it finds itself on the verge of collapse. Violations of basic rights are a part of routine. The solution for the approaching chaos installed in the prison system is the privatization of prisons. Gradually applied, it began with the provision of means services, such as food, cleaning and health. However, in 2013, the first completely private penitentiary is inaugurated, from the project to the conclusion of the work, and execution of the service. I was developed in the public-private partnership model. However, the proposal is not innovative, as it ignores matters of social character, which are intrinsic to prison reality in Brazil. The criminal selectivity bordered by social stratification. The economic options that generate the massification of the collective. Organized crime and violence promoted by it. They are hidden tensors of the political proposals that are based on the economic aspect. The present work is guided by bibliographic research, uses historical and hypothetical deductive methods. It seeks to contribute with critical thinking regarding the proposals that aim to minimize the disorder installed in prisons.